Desglobalization : the future of growth in the international economy? - Sánchez Flores, Rebeca; Serna, Germán (My University, 2022)
Sustainable development has been an important topic to supply chain management. Cultural thoughts and new trends have influenced the design and execution of operations along logistics and distribution channels to cope with new regulations in order to satisfy customer requirements without compromising resources, needs and welfare of new generations. Therefore, the purpose of this chapter is to present insights of current literature on sustainability and its relationship to deglobalization from a value chain perspective by identifying strategic decisions taken by organizations. The chapter provides an overview of sustainability as a key element on current value chain operations. Then, the discussion focusses on unfolding empirical research developed by experts and academics on the topic. Furthermore, deglobalization strategies for value chains are analyzed, followed by a description of technological solutions as crucial means to achieve business growth and competitiveness. Finally, a conceptual model is proposed to achieve sustainable development within a deglobalized environment and value chain performance enhancement along the entire firm’s operations. Conclusions are presented, summarizing the contribution of this chapter and highlighting the need for sustainable practices when planning for value chain growth within a deglobalized scenario. Future research suggestions are provided to progress on deglobalization as a strategy and means for value chain growth under existing market uncertainty.
Sustainability as a Deglobalization Strategy for Value Chains Growth
Keywords: Sustainability; Supply chain; Value chain; Strategy; Deglobalization; Campus Mexicali